Efficient public adaptation to climate change: An investigation of drivers and barriers from a Public Choice perspective - Erik Gawel; Clemens Heuson; Paul Lehmann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2012)
Since numerous countries have already initiated a process of adaptation to climate change by drafting strategies or catalogues of measures, it is of particular importance to identify and overcome potential barriers to efficient public adap-tation from the beginning. A major source of barriers is given by self-interest driven behaviour of actors involved in the adaptation policy process. This is for the reason that several features of the adaptation option and the surrounding policy framework, such as the lacking of a clear-cut success-metric, are likely to boost such behaviour since they facilitate both the manipulation of the adaptation output and the exertion of influence through the various actor groups shaping the political system. Against this background, this paper provides a broad conceptual Public Choice theory framework serving both for raising the consciousness of potential barriers to efficient public adaptation and creating a sound basis for further in-depth research. Concerning the efficiency of public adaptation policies, we distinguish three dimensions, namely extent, structure (form and timing) and organisation (vertical and horizontal) of public adaptation. For either case, potential political biases are investigated taking into consideration the self-interests and influence of voters, pressure groups, bureaucrats and politi-cians in a representative democracy framework.
Keywords: D78; Q54; Q58; 330; adaptation; barriers; climate change; climate policy; efficiency; public choice